Dimensi Pembentuk Ketertarikan Investor Memilih Produk Cilem BSI Kencong - Nadia Silviatus Sa’diya; Uliyatul Mu’awwanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic investment has become an attractive choice for Indonesian society looking to grow their funds while adhering to Islamic law. BSI Kencong, part of Bank Syariah Indonesia (BSI), offers the Cilem investment product designed to meet these needs. This research aims to identify the factors influencing public interest in investing in Cilem at BSI Kencong. The research method employed is qualitative, utilizing literature review and customer testimonial analysis. Data was gathered from various sources, including official BSI publications, Islamic investment literature, and customer reviews. The findings reveal several key factors driving public interest in Cilem investments. Firstly, the competitive profit potential is a major attraction, supported by expertise in investment management and diversification across safe Sharia-compliant instruments. Secondly, the security and trust provided by BSI Kencong, overseen by the Financial Services Authority and the National Sharia Board of MUI, instill confidence in customers. Thirdly, adherence to Islamic principles is crucial, evidenced by Sharia certification from the National Sharia Board of MUI. Additionally, ease of access and transactions play a significant role. BSI Kencong offers various channels including branches, the BSI Mobile app, website, and agents, enhancing customer convenience. Friendly and professional service from BSI Kencong staff adds to customer comfort and satisfaction. Active promotion and education efforts by BSI Kencong increase public awareness and understanding of Cilem products. Positive testimonials from investors demonstrate real benefits, encouraging prospective customers to participate. Lastly, the desire to support the growth of Islamic economy in Indonesia further strengthens public interest in Cilem investments. In conclusion, the combination of factors such as profit potential, security and trust, Sharia compliance, ease of access, professional service, promotion and education, positive testimonials, and support for Islamic economy collectively create a compelling attraction for the public to invest in Cilem products through BSI Kencong.